2019
DOI: 10.2478/jomb-2018-0038
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of long non-coding RNA growth arrest-specific 5 in the remission induction therapy in childhood acute lymphoblastic leukemia

Abstract: Summary Background Long non-coding RNA growth arrest-specific 5 (GAS5) is deregulated in many cancers because of its role in cell growth arrest and apoptosis. Additionally, GAS5 interacts with glucocorticoid receptor, making it a potential pharmacotranscription marker of glucocorticoid (GC) therapy. In this study, we aimed at analysing GAS5 expression in the remission induction therapy phase of childhood acute lymphoblastic leukemia (ALL), in which GCs are mandatorily used, and to correlate it with therapy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
1
21
1
Order By: Relevance
“…GAS5 expression was recently found to be tightly linked to therapy progression in acute lymphoblastic leukemia (ALL) [ 30 ]. In the study of Gasic et al [ 30 ], GAS5 expression was reduced at day 33 of the induction therapy as compared to day 15, yet with still higher levels, compared to the time of diagnosis. This report suggested two interesting findings.…”
Section: Gas5 In Tumor Therapy-related Resistanmentioning
confidence: 99%
“…GAS5 expression was recently found to be tightly linked to therapy progression in acute lymphoblastic leukemia (ALL) [ 30 ]. In the study of Gasic et al [ 30 ], GAS5 expression was reduced at day 33 of the induction therapy as compared to day 15, yet with still higher levels, compared to the time of diagnosis. This report suggested two interesting findings.…”
Section: Gas5 In Tumor Therapy-related Resistanmentioning
confidence: 99%
“…The aging of hemato poietic cells, caused by both endogenic and exogenic cellular factors, disrupted hematopoietic environments, self-restoration, and regeneration, is related to immune system reconfiguration and the increase in leukemia incidence. Ghoti et al (14) reported oxidative stress in erythrocytes, thrombocytes, and polymorphonuclear leukocytes and increased serum ROS levels in low-risk MDS patients. In addition, in another study, it was shown that this oxidative situation is related to the significant increase in oxidative DNA damage in BM cells in MDS patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that cancer cells adapt to oxidative conditions by elevating their antioxidant capacities, decreasing the ability to regulate other changes in oxidative stress compared to normal cells. The elevation of antioxidants as an adaptation to intracellular oxidative stress is a well-known phenomenon (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…However, some results have been reported. The long noncoding RNA GAS5 was shown to be associated with a poor GCs response in childhood ALL during remission induction therapy [38]. GAS5 imitates the glucocorticoid response element (GRE) sequence, which is a DNA sequence to which the GC-GR complex needs to bind to in order to realize its effect, thus GAS5 can bind the GC-GR complex and stop it from binding to the GRE sequence [39].…”
Section: Glucocorticoid Drugsmentioning
confidence: 99%